Analisis Kemampuan Berpikir Kreatif dan Koneksi Matematis Siswa pada Materi Segiempat dan Segitiga Ditinjau dari Self-Concept Matematis Siswa - Muhammad Rico Aulya; Nizaruddin Nizaruddin; Rizky Esti Utami (Perkumpulan Kualitama Edukatika Indonesia, 2023)
This study aims to describe students creative thinking abilities and mathematical connections in the quadrilateral and triangle material in terms of students mathematical self-concept. This type of research is descriptive research with a qualitative approach. The subjects of this study consisted of 29 students in class VIII E of SMP NEGERI 1 KALIWUNGU who were then selected based on the self-concept scale, namely 3 students with high self-concept, 3 students with moderate self-concept and 3 students with low self-concept. Data collection was carried out using a self-concept scale, written tests, interviews and documentation. Data analysis techniques were carried out in 3 stages, namely data reduction, data display and conclusion/verification. The validity of the data using technique triangulation and source triangulation. The analysis was developed based on indicators of creative thinking skills and mathematical connections by taking into account self-concept. Based on the results of the analysis it is known that subjects with high self-concept abilities are able to fulfill all indicators of creative thinking and all indicators of mathematical connection, subjects with moderate self-concept are able to fulfill three aspects of creative thinking ability, namely thinking fluently, thinking flexibly, thinking in detail and being able to fulfill all indicators of connection mathematically, subjects with low self-concept are unable to fulfill all indicators of creative thinking and all indicators of mathematical connection.